Peningkatan Kualitas Sumber Daya Manusia Melalui Problem-Based Learning (PBL) - Nuryasman MN (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2001)
The need for qualified human resources has always been a decisive factor in a country to be competitive in the global context. From the quantitative aspect there is an abundant amount of humen resources, but qualified ones having the necessary skills and professional staff/workers is prevailing. To meet the needs for qualified people, education as a process is important and a new concept called â€œproblem based learningâ€ will be useful for this purpose.